Determination and Review of Physical and Mechanical Properties of Raw and Treated Coconut Fibers for Their Recycling in Construction Materials - Huyen Bui; Nassim Sebaibi; Mohamed Boutouil; Daniel Levacher (Fibers, 2020)
In order to reduce the dependency on conventional materials and negative environmental impacts, one of the main responsibilities of the construction field is to find new eco-friendly resources to replace the traditional materials partially. Natural fibers were known as potential candidates for the reinforcement of structures in civil engineering by virtue of their advantages. Among the different kinds of vegetable fibers, coconut fiber has been exploited in a limited way over the past few years. This paper aims at evaluating the different properties of local coconut fibers (Vietnam). Several laboratory tests provide geometrical, physical, mechanical properties and durability properties that are compared with literature results obtained from similar natural fibers. The local coconut fibers tested demonstrated properties suitable for reinforced mortars. With adequate control of their preparation, they could be reused in the manufacture of mortars in the construction.